Análise de mutações somáticas na proteína precursora de amilóide e genotipagem da apolipoproteína em pacientes com diagnóstico definitivo de doença de Alzheimer - Joao Carlos Barbosa Machado (1996)
The molecular basis for sporadic Alzheimer's disease remains largelyunknown, but amyloid deposition in specific brain areas is thought to play a role in disease pathogenesis. The deposited protein is the proteolytic cleavage product of a large precursor protein- Amyloid Precursor Protein (APP). In a small subset of familial Alzheimer's disease patients, germline mutations in exons 16 and 17 of the APP gene were demonstrated, and at least one such mutation was shown to be responsible for histological Alzheimer's disease phenotype intransgenic mice. We hypothesized that in some cases of sporadic Alzheimer's disease, a somatic mutation in an embryonic cell committed to neuronal development within the APP gene may result in Alzheimer's disease phenotype. A precedent for a somatic, mosaic pattern of mutation has been demonstrated within the Gs Alpha gene in affected tissues of patients with McCune-Albright syndrome. Futhermore, germline mutations that are encountered in familial cancer cases, similarly occur somatically in the tumors of sporadic cases. Usingthe polymerase chain reaction (PCR) and denaturing gradient gelelectrophoresis (DGGE) complemented by direct DNA sequencing of the PCR products, we analyzed exons 16 and 17 of the APP gene in 99 brain tissues from patients with histopathologically proven Alzheimer's disease. As a positive control, we used a germline mutation from a Swedish family with a double germline mutation in exon 16 (codon 670/671). No migration abnormalities were demonstrated in any sample in either exon, whereas the known mutation was easily detected as an abnormally migrating band. Sequence analysis of exons 16 and 17 in two samples did not reveal any sequence alterations. Genotyping of the Apolipoprotein E alleles in these brains was E3 - 73.9%, E4- 22.4% e E2-3%, an unexpected result based on some (but not all) studies showing a strong association of sporadic Alzheimer's disease and the E4 allele.We conclude that mutations in the regions of the APP gene coding for theamyloid deposited in the brain do not display somatic mutations and that other mechanisms leading to amyloid deposits may be operative.